Sleep Disorders in Pregnancy, Influencing Factors and Quality of Life - Kadıoğlu, Nezaket; Sert, Umit Yasemin; Sariaslan, Seval Gundogdu; Mursel, Konul; Celen, Sevki (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Aim In our study, the frequency of sleep disturbances in pregnancy, the reasons underlying the low quality of sleep, clinical factors, and the effects on quality of life were investigated.Methods The study was planned as a prospective study and included 189 pregnant women. Clinical features, laboratory results, socio-demographic status, obstetric and medical anamnesis were evaluated. The Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, the Berlin Questionnaire, Beck Depression Inventory, SF-36 quality-of-life questionnaire, and restless leg syndrome (RLS) diagnosis criteria were used for data collection.Results We investigated sleep disorders in 110 pregnant women (58.2%). A history of premenstrual syndrome and patients with hyperemesis gravidarum, obstructive sleep apnea syndrome, Vitamin B12 deficiency, and higher TSH levels in the laboratory were found to be associated with sleep disorders. Sleep disorders and daytime sleepiness were associated with depression, physical and social functioning, pain, and disturbance in general health perception. The number of pregnant women who had two or more RLS complaints was 84 (44%).Conclusion The results of our study show that sleep disorders in pregnancy can be managed with easily applicable methods according to the risk factors and related problems.
Keywords: Depression; Quality of life; Pregnancy; Sleep disorders